Variasi Genetik Spesies Mangrove Ceriops tagal berdasarkan Marka RAPD - Dhuta Sukmarani (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
Ceriops tagal are found at Segara Anakan Cilacap, Baluran National Park and Karimunjawa National Park. Information on the genetic diversity can be used for conservation policy. Genetic variation of C. tagal were analysed by using Random Amplified Polymorphic DNA (RAPD). This study aims to determine the genetic variation in each population and between populations C. tagal based on RAPD markers. The total DNA was extracted with CTAB extraction method. Amplification was performed using 10 primer (OPA-3, OPA-10, OPB-1, OPB-6, OPB-7, OPB-8, OPB-10, OPB-12, OPB-17 and OPB-18). Amplification includes pradenaturation at 94°C for 5 min, followed by 45 cycles of denaturation at 94°C for 1 min, primer annealing at 37°C for 1 min, and primer elongation on 72°C for 1 min 30 sec, final extension at 72°C for 5 min and ends with holding at 4°C for 1 min. The analysis was done by changing the pattern of fragments to binary data (for bands appear =